A QUALITATIVE RESEARCH METHODOLOGY TO EXAMINE THE EFFECTIVENESS OF A PROJECT-BASED APPROACH IN TEACHING ESP (Analysis of International Sciences, 2024)
English for Specific Purposes (ESP) is a specialized form of English language instruction that requires teaching approaches tailored to the specific needs and goals of the learners. This article explores the role of a project-based approach in teaching ESP. The project-based approach involves giving students a project to work on that is related to their specific area of study. The article reviews the literature on project-based learning in ESP and discusses the benefits of using this approach, including increased motivation and engagement, the development of critical thinking and problem-solving skills, and the integration and holistic development of language skills. A qualitative research methodology is employed to investigate the effectiveness of the project-based approach in teaching ESP, with data collected through student interviews, classroom observations, and analysis of student projects. The results of the study support the use of project-based learning as an effective approach to teaching ESP. The article concludes by discussing the importance of designing the project carefully and providing the necessary teacher support and guidance to ensure success.